Studied on 2-Aminpyridine Molecule by FTIR and Laser Raman Spectroscopy - Mohan, S.; Ilangovan, V. (Asian Journal of Chemistry, 2010)
Laser Raman and FTIR spectra of 2-aminopyridine were recorded in the range of 4000–100 cm–1 and 4000–500 cm–1 , respectively. Vibrational assignments have been made for many observed frequencies on the basis of CS point group symmetry, group frequency consideration as well as comparison with accepted assignments for certain vibrational modes in other compounds with structural similarities and normal coordinate analysis. The potential energy distributions were also obtained. The results are briefly discussed.